Koopetycja - przejaw przeobrażeń we współczesnej praktyce zarządzania - Rzońca, Waldemar (Coopetition - a sign of changes in the present-day management practice, 2005)
In the paper the problems of coopetition, the simultaneous cooperation and competition with the same enterprise, are discussed. The reasons for the spread of this phenomenon in the present-day economy are named, various typologies of firm coopetition are presented, and the results of chosen investigations carried out on the use of coopetition in business are discussed. Moreover, the existing gap between the relatively common use of coopetition in practice and poor scientific achievements in this field is pointed out.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1092, s. 83-90